Dynamic assessment of phonological awareness in monolingual and bilingual French-speaking children. - Kehoe, Margaret; Matrat, Mélodie; Delage, Hélène (Clinical Linguistics & Phonetics, 2025)
Dynamic assessment (DA) is a tool used to assess children's learning potential. Research on English-speaking children indicates that DA effectively diagnoses language disorders in monolingual and bilingual children. However, few DAs have been developed for French-speaking children. This study aimed to examine the validity of a dynamic phonological awareness task for differentiating French-speaking monolingual and bilingual children with and without developmental language disorder (DLD). Thirty-eight monolingual and bilingual children, aged 4–8 years, 23 with typical development (TD) and 15 with DLD, participated in the study. They performed a dynamic phoneme segmentation task, in which graduated cues were provided. Children were also administered a nonword repetition (NWR) task, and a modifiability scale, in which the examiner rated the child's responsivity during the task. Statistical analyses examined what factors influenced dynamic task performance, and calculated the sensitivity and specificity of the tests. Results indicated that four factors emerged as significant in a mixed-effects logistic regression model: age, diagnostic group (TD vs. DLD), modifiability, and the number of phonemes in the target word. Older children who had TD and higher modifiability scores had better segmentation skills than other children. Words with fewer phonemes were also easier to segment than words with greater numbers of phonemes. The dynamic task had good sensitivity in the identification of DLD but less good specificity. Our findings indicate that a dynamic task of phonological awareness has the potential to be used as a diagnostic tool to differentiate TD and DLD.